Community health priorities: Lessons for malaria prevention from Balaka district, Malawi - Parker, Warren (Malawi Med J, 2018)
INTRODUCTION: Communication to address priority health challenges typically draws on epidemiological research in conjunction with referencing global and country strategies. While community-level perspectives on health challenges typically align with national priorities, nuances and barriers that constrain health response may be less well known. To deepen understanding of the relation between situational aspects of health and ways of making meaning, community insights into health priorities were explored. METHODS: Action Media, an established participatory research methodology for informing health communication design and strategy, was undertaken with parents of children under 5 in Balaka District, Malawi. RESULTS: Participants identified malaria as a priority concern in their community. While it was reported that there was strong commitment to consistent use of long lasting insecticide treated nets, there was frustration that malaria incidence remained high. It was observed that risk of exposure to mosquito bites was increased as a result of chores and other activities that extended into the early evenings prior to retiring to bed under a bed net. Bed bug infestations were said to be a common and ongoing concern. Some community members alleviated discomfort by abandoning their beds and sleeping outside without adequate protection while others boiled their bed nets to remove bed bugs. Accessing distant health facilities when ill with malaria was difficult for adults and children. Participants identified the need for effective strategies to address these concerns including accessing mosquito repellant, eradicating bed bugs, treating malaria locally and collaborating in malaria control activities. CONCLUSIONS: Meeting targets for malaria prevention requires consideration of contextual factors that undermine effective malaria prevention in affected communities. Such factors are not immediately apparent through epidemiological data. Regularly assessing contextual challenges in high malaria incidence areas provides opportunities to understand gaps, to refine intervention strategies and to inform communication programming.